The Design, Development, and Evaluation of an Education Programme for Families of Trans Young People: A Community-Based Participatory Research Study - SHAREK, DANIKA BURKE (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2018)
Background and Aim: When a young person identifies as trans(gender), this may raise issues for the entire family. Access to appropriate education and information has been shown to positively impact on families of trans young people, however, there is a lack of educational opportunities for these families, particularly within the Republic of Ireland. The aim of this study was to explore and address the trans-related education needs of families of trans young people in the Republic of Ireland. Methodology: Informed by the transformative paradigm, social justice was central to this study, particularly the principles of respect and beneficence. The guiding methodology for the study was Community-Based Participatory Research, a collaborative partnership approach to working with and for a community with a focus on real world, sustainable solutions. Study Design and Methods: A three-phase multiphase design was used to explore and address families? trans-related education needs. Phase 1 explored families? trans-related education experiences and needs through a consultation process using qualitative surveys and qualitative interviews with professionals, family members, and trans young people. Phase 2 focused on the design and development of an online education programme (titled ?GenderEd.ie?) to address families? education needs. Phase 3 employed a convergent, mixed methods approach to evaluate the education programme using quantitative surveys to assess the impact of the education programme and qualitative interviews to explore families? experiences with the programme. Findings: The Phase 1 findings provided evidence of the need for an education programme for families of trans young people in the Republic of Ireland, with participants making a number of recommendations to inform the design of the education programme. The Phase 2 design process was guided by a seven-step, learner-centred, outcomes-based approach to module design, which included a participatory evaluation with educational specialists, professionals, families of trans young people, and trans young people. The design process resulted in the development of ?GenderEd.ie?, an eight-module online education programme, which aimed to provide basic information to families of trans young people in the Republic of Ireland. In Phase 3, eight family members completed the pre-education programme and post-education programme surveys and eight family members participated in interviews. Statistically significant changes were found in terms of overall scores on trans-related knowledge from pre-education programme to post-education programme, and on six of the individual knowledge topics. No statistically significant changes were found on any of the other measures. Interview participants described the positive aspects of the programme, including that it was easy-to-use and accessible, with comprehensive trans-related information. The majority of interview participants reported learning something new from the programme; however, they reported fewer soft skills gained from the programme. Discussion and Conclusion: The findings from this study add to the international literature concerning families? trans-related education needs. Of importance, this is the first study to document the participatory design and development of an education programme to address families? trans-related education needs. In addition, this study provides robust evidence of the impact of an education programme on families? trans-related knowledge. The study was limited by the use of non-probability convenience sampling methods based on a small, non-representative sample of those most likely to be supportive of a trans family member. The findings have implications in terms of theory, policy, service development, and education and practice. The study also highlights a number of opportunities for future research. In conclusion, this study has demonstrated that an education programme designed and developed through participatory methods has the potential to help positively support families and trans young people.
APPROVED
Keywords: Transgender; Family; Education; Evaluation; Community-Based Participatory Research